Empreendedorismo institucional: um estudo de caso sobre o polo gastronômico de Santa Felicidade, Curitiba, PR, Brasil - Vieira, Danielle Ferraz (2021)
The organizational field is the result of interactions over time between organizations, individuals and the context in which it is inserted. The foundations of the new institutional theory allow this reading and, in this sense, considering the theme of institutional entrepreneurship, the objective of this research was to understand how institutional entrepreneurship actions influenced the formation of the organizational field of the Gastronomic Pole in the Santa Felicidade District, in the city from Curitiba, Capital of Paraná, Brazil. To achieve this objective, a qualitative research strategy was adopted, through the case study method, whose object of study is the touristgastronomic sector of the referred neighborhood. An analysis was carried out through a sectional profile with longitudinal approximation in the period from 1920 to 2020. As data collection techniques were: documentary research and semistructured interviews, applied for the founders, owners and employees of the associations that made up the sample. The data were analyzed using a thematic content analysis technique, according to Bardin (2011). In order to establish an approximation with the empirical field, a documentary research was undertaken. The recent data were then tensioned with a theory, resulting in the analytical categories: institutional entrepreneurship (DIMAGGIO, 1988) at the action level; institutions (GREENWOOD et al., 2008) at the institutional context level; and organizational field (DIMAGGIO; POWELL, 2005; SCOTT, 1994). Later, after collecting primary data, the categories were subdivided considering: the precipitating events (GREENWOOD; SUDDABY; HININGS, 2002); as institutional entrepreneurship actions (DORADO, 2013); social practices supported by cultural-cognitive, normative and regulatory elements (SCOTT, 2008); the relevant social actors (DIMAGGIO; POWELL, 2005); and the different stages of the organizational field (HARDY; MAGUIRE, 2008). According to the findings, it is considered that institutional entrepreneurship actions performed by social actors identified in this field (both individuals, groups and organizations) resulted in numerous social practices. Among these, some have become perennial reaching the level of an institution. As a result, institutional changes occurred, culminating in both the creation and maintenance of institutions. Although institutional diffusion has been largely carried out of a bottom-up nature, social practices resulting from pressures of a top-down nature were also identified. Thus, it is concluded that: institutional entrepreneurship actions allowed the creation of specifications aimed at gastronomy, through social practices that were widely disseminated in the sector. The organizational field, initially focused on agricultural production, was reconfigured as new practices became institutionalized. Currently, it is a mature and legitimate organizational field, it has become a Gastronomic Pole and tourist destination, sought after due to its restaurants, wineries and wicker craft stores. In view of this, the main theoretical contribution of this study went beyond supporting the development of the theory on institutional entrepreneurship, demonstrating that institutions are gradually established, as predicted by Mahoney and Thelen (2010). In terms of practical contribution, the institutionalization of the Santa Felicidade Gastronomic Pole was verified, similar to what happens in other clusters.